Pathophysiology of myelin oligodendrocyte glycoprotein antibody disease - Corbali, Osman; Chitnis, Tanuja (Frontiers in Neurology, 2023)
Myelin Oligodendrocyte Glycoprotein Antibody Disease (MOGAD) is a spectrum of diseases, including optic neuritis, transverse myelitis, acute disseminated encephalomyelitis, and cerebral cortical encephalitis. In addition to distinct clinical, radiological, and immunological features, the infectious prodrome is more commonly reported in MOGAD (37-70%) than NMOSD (15-35%). Interestingly, pediatric MOGAD is not more aggressive than adult-onset MOGAD, unlike in multiple sclerosis (MS), where annualized relapse rates are three times higher in pediatric-onset MS. MOGAD pathophysiology is driven by acute attacks during which T cells and MOG antibodies cross blood brain barrier (BBB). MOGAD lesions show a perivenous confluent pattern around the small veins, lacking the radiological central vein sign. Initial activation of T cells in the periphery is followed by reactivation in the subarachnoid/perivascular spaces by MOG-laden antigen-presenting cells and inflammatory CSF milieu, which enables T cells to infiltrate CNS parenchyma. CD4+ T cells, unlike CD8+ T cells in MS, are the dominant T cell type found in lesion histology. Granulocytes, macrophages/microglia, and activated complement are also found in the lesions, which could contribute to demyelination during acute relapses. MOG antibodies potentially contribute to pathology by opsonizing MOG, complement activation, and antibody-dependent cellular cytotoxicity. Stimulation of peripheral MOG-specific B cells through TLR stimulation or T follicular helper cells might help differentiate MOG antibody-producing plasma cells in the peripheral blood. Neuroinflammatory biomarkers (such as MBP, sNFL, GFAP, Tau) in MOGAD support that most axonal damage happens in the initial attack, whereas relapses are associated with increased myelin damage.